Validating assumptions in calculating carbon dioxide removal by enhanced rock weathering in Kantola et al., 2023 - Adam Wolf; Elliot Chang; Ilsa B. Kantola; Elena Blanc‐Betes; Michael D. Masters; Alison Marklein; Caitlin E. Moore; Carl J. Bernacchi; Evan H. DeLucia (Global Change Biology, 2024)

Improved net carbon budgets in the US Midwest through direct measured impacts of enhanced weathering - Ilsa B. Kantola; Elena Blanc‐Betes; Michael D. Masters; Elliot Chang; Alison Marklein; Caitlin E. Moore; Adam von Haden; Carl J. Bernacchi; Adam Wolf; Dimitar Z. Epihov; David J. Beerling; Evan H. DeLucia (Global Change Biology, 2023)
Terrestrial enhanced weathering (EW) through the application of Mg‐ or Ca‐rich rock dust to soil is a negative emission technology with the potential to address impacts of climate change. The effectiveness of EW was tested over 4 years by spreading ground basalt (50 t ha −1 year −1 ) on maize/soybean and miscanthus cropping systems in the Midwest US. The major elements of the carbon budget were quantified through measurements of eddy covariance, soil carbon flux, and biomass. The movement of Mg and Ca to deep soil, released by weathering, balanced by a corresponding alkalinity flux, was used to measure the drawdown of CO 2 , where the release of cations from basalt was measured as the ratio of rare earth elements to base cations in the applied rock dust and in the surface soil. Basalt application stimulated peak biomass and net primary production in both cropping systems and caused a small but significant stimulation of soil respiration. Net ecosystem carbon balance (NECB) was strongly negative for maize/soybean (−199 to −453 g C m −2 year −1 ) indicating this system was losing carbon to the atmosphere. Average EW (102 g C m −2 year −1 ) offset carbon loss in the maize/soybean by 23%–42%. NECB of miscanthus was positive (63–129 g C m −2 year −1 ), indicating carbon gain in the system, and EW greatly increased inorganic carbon storage by an additional 234 g C m −2 year −1 . Our analysis indicates a co‐deployment of a perennial biofuel crop (miscanthus) with EW leads to major wins—increased harvested yields of 29%–42% with additional carbon dioxide removal (CDR) of 8.6 t CO 2 ha −1 year −1 . EW applied to maize/soybean drives a CDR of 3.7 t CO 2 ha −1 year −1 , which partially offsets well‐established carbon losses from soil from this crop rotation. EW applied in the US Midwest creates measurable improvements to the carbon budgets perennial bioenergy crops and conventional row crops.

Vulnerability of field crops to midcentury temperature changes and yield effects in the Southwestern USA - Emile Elias; Alison Marklein; John T. Abatzoglou; Jake Dialesandro; Joel Brown; Caiti Steele; Albert Rango; Kerri Steenwerth (Climatic Change, 2018)

Mineralization ratios of nitrogen and phosphorus from decomposing litter in temperate versus tropical forests - Alison R. Marklein; Joy B. Winbourne; Sara K. Enders; David J. X. Gonzalez; Tiff L. van Huysen; Jorge E. Izquierdo; Derrick R. Light; Daniel Liptzin; Kimberley E. Miller; Scott L. Morford; Robert A. Norton; Benjamin Z. Houlton (Global Ecology and Biogeography, 2016)
Aim Terrestrial ecosystems sequester about 25% of anthropogenic CO 2 emissions annually; however, nitrogen ( N ) and phosphorus ( P ) limitation of plant productivity and microbial functioning could curtail this key ecosystem service in the future. Our aim is to address variations in nutrient resupply during decomposition – especially whether the N : P ratio of nutrient recycling via mineralization varies within and across diverse forest biomes. Location Global forest ecosystems. Methods We compiled data on in situ litter decomposition experiments (leaf, wood and root) from the primary literature to examine the relationships between net N and P mineralization across temperate versus tropical forests world‐wide. We define net nutrient mineralization ratios as the average N : P released from decomposing substrates at a given ecosystem site. Results We show that net N and P mineralization are strongly correlated within biomes, suggesting strong coupling between N and P recycling in forest ecosystems. The net N : P of leaf‐litter mineralization is higher in tropical forests than in temperate forests, consistent with latitudinal patterns in foliar and leaf‐litter N : P . At the global scale, the N : P of net mineralization tracks, but tends to be lower than that of litter N : P , pointing to preferential P (versus N ) mineralization in forest ecosystems. Main conclusions Our results do not support the view that there is a single, globally consistent mineralization N : P ratio. Instead, our results show that the N : P of net mineralization can be predicted by the N : P of litter, offering a method for incorporating P into global‐scale models of carbon–nutrient–climate interactions. In addition, these results imply that P is scarce relative to microbial decomposer demands in tropical forests, whereas N and P may be more co‐limiting when compared with microbial biomass in the temperate zone.

Relationships among net primary productivity, nutrients and climate in tropical rain forest: a pan‐tropical analysis - Cory C. Cleveland; Alan R. Townsend; Philip Taylor; Silvia Alvarez‐Clare; Mercedes M. C. Bustamante; George Chuyong; Solomon Z. Dobrowski; Pauline Grierson; Kyle E. Harms; Benjamin Z. Houlton; Alison Marklein; William Parton; et al. (Ecology Letters, 2011)
Ecology Letters (2011) 14 : 939–947 Abstract Tropical rain forests play a dominant role in global biosphere‐atmosphere CO 2 exchange. Although climate and nutrient availability regulate net primary production (NPP) and decomposition in all terrestrial ecosystems, the nature and extent of such controls in tropical forests remain poorly resolved. We conducted a meta‐analysis of carbon‐nutrient‐climate relationships in 113 sites across the tropical forest biome. Our analyses showed that mean annual temperature was the strongest predictor of aboveground NPP (ANPP) across all tropical forests, but this relationship was driven by distinct temperature differences between upland and lowland forests. Within lowland forests ( k ), soil N and soil respiration were all directly related with total surface (0–10 cm) soil P concentrations. Our analysis provides some evidence that P availability regulates NPP and other ecosystem processes in lowland tropical forests, but more importantly, underscores the need for a series of large‐scale nutrient manipulations – especially in lowland forests – to elucidate the most important nutrient interactions and controls.